LOWER-LIMB ASYMMETRY IN BALANCE ABILITY OF YOUNG BADMINTON PLAYERS - Anna Manolova (Scientific Publishing House. NSA Press, 2018)
Based on the limited evidence available about balance performance among young badminton players, this study was aimed to establish the presence or absence of lower-limb balance asymmetry among 13-15 years old players. The research was done among 40 young players (22 girls, 18 boys) from 3 Bulgarian clubs. Uni-pedal stance test and Y balance test were used to determine balance abilities. Paired sample T test and Wilcoxon signed-rank test were used to evaluate the data from the dominant and non-dominant leg. The results from the two tests show that there is no statistically significant difference between the legs. These results support the usefulness of performing bilateral balance exercises, so that the asymmetry that players are predisposed to develop could be reduced and the risk of lower extremity injuries would be decreased.